Inclusion of glycerol in forage diets increases methane production in a rumen simulation technique system. Issue 5 (14th March 2014) - Avila-Stagno, Jorge; Chaves, Alexandre V.; O. Ribeiro, Gabriel; Ungerfeld, Emilio M.; McAllister, Tim A.
<x content-type="archive" xml:space="preserve">Abstract</x> We hypothesised that the inclusion of glycerol in the forage diets of ruminants would increase the proportion of propionate produced and thereby decrease in vitro CH4 production. This hypothesis was examined in the present study using a semi-continuous fermentation system (rumen simulation technique) fed a brome hay (8·5 g) and maize silage (1·5 g) diet with increasing concentrations (0, 50, 100 and 150 g/kg DM) of glycerol substituted for maize silage. Glycerol linearly increased total volatile fatty acids production (P< 0·001). Acetate production was quadratically affected (P= 0·023) and propionate and butyrate production was linearly increased (P< 0·001). Glycerol linearly increased (P= 0·011) DM disappearance from hay and silage. Crude protein disappearance from hay was not affected (P= 0·789), but that from silage was linearly increased (P< 0·001) with increasing glycerol concentrations. Neutral-detergent fibre (P= 0·040) and acid-detergent fibre (P= 0·031) disappearance from hay and silage was linearly increased by glycerol. Total gas production tended to increase linearly (P= 0·061) and CH4 concentration in gas was linearly increased (P< 0·001) by glycerol, resulting in a linear increase (P< 0·001) in mg CH4/g DM digested. Our hypothesis was rejected as increasing concentrations of glycerol in a forage diet linearly increased CH4 production in semi-continuous fermenters, despite the increases in the concentrations of propionate. In conclusion, this apparent discrepancy is due to the more reduced state of glycerol when compared with carbohydrates, which implies that there is no net incorporation of electrons when glycerol is metabolised to propionate.